MOSES’ MOTHER IN EXODUS 2:1-10 AND MOTHERS IN PERSONAL NAMES AMONG THE IGBO PEOPLE, SOUTH-EAST NIGERIA - Obiorah, M.J.; Okafor, N.C. (Acta Theologica, 2020)
In cultures such as Ancient Israel and the Igbo people of South-eastern Nigeria, the qualities of women and the essential roles they play in society are elucidated in various ways. The Hebrew Bible conveys these in narratives, while the Igbo people do so in female personal names. This article presents the role Moses’ mother played in saving him (Ex. 2:1-10) and similar actions of mothers in Igboland, as encoded in female personal names. Narrative analysis is employed in the study of the biblical text. The explanatory analysis of Igbo personal names uses data collected from families who give and bear such names. This article aims to uplift the excellent roles of women and demonstrates that patriarchy does not obliterate those contributions in society.